The Influence of Internal Control and User Competence on the State Treasury and Budget Information System (SPAN) in the Veterans Administration Development Agency and Kodam Reserves - Kartika Pratiwi Putri; Mochamad Zakaria; Hendri Maulana (Greenation International Journal of Economics and Accounting, 2023)
The purpose of this study was to find out and analyze: The Influence of Internal Control and User Competence on the State Treasury and Budget Information System (SPAN) in the Veterans Administration Advisory Board and Kodam Reserves, either simultaneously or partially. The research method used in this study was a descriptive survey and an explanatory survey. The unit of analysis in this study were employees at the Veterans Administration and Reserve Military Command Board with a sample of 50 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that Internal Control and User Competence simultaneously affect the State Treasury and Budget Information System (SPAN) in the Veterans Administration Advisory Board and Kodam Reserves. However, partially the dominant Internal Control influences the State Treasury and Budget Information System (SPAN) rather than User Competence